THE DIVERSITY OF SOIL MACROFAUNA ON THE BURNED AND UNBURNED LAND IN THE RUMBIO CUSTOMARY FOREST - Darwan Suganda; Defri Yoza; Wardati (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2020)
Soil macrofauna is a part of soil biodiversity that plays an important role in the improvement soil physical, chemical and biological properties. Fires that occur will affect the activity and presence of soil macrofauna which helps the decomposition process of organic materials such as providing better environmental facilities (Micro Habitat). This research aims to know species diversity and population density of soil macrofauna on burned and unburned land in The Rumbio Customary Forest. The research was carried out in The Rumbio Customary Forest and the Soil Laboratory Faculty of Agriculture University of Riau. The sampling of soil macrofauana was carried out on burned and unburned land in The Rumbio Customary Forest and also for measurement of soil physical-chemical factors. The research used the hand sorting method. This research showed that the population density of soil macrofauna on unburned land is higher if compared to burned land.